Use of antenatal corticosteroids at health facilities and communities in low-and-middle income countries. Issue 1 (December 2016) - Berrueta, Mabel; Hemingway-Foday, Jennifer; Thorsten, Vanessa; Goldenberg, Robert; Carlo, Waldemar; Garces, Ana; Patel, Archana; Saleem, Sarah; Pasha, Omrana; Chomba, Elwyn; Hibberd, Patricia; Krebs, Nancy; et al.
Abstract Background Antenatal corticosteroids (ACS) for women at high risk of preterm birth is an effective intervention to reduce neonatal mortality among preterm babies delivered in hospital settings, but has not been widely used in low-middle resource settings. We sought to assess the rates of ACS use at all levels of health care in low and middle income countries (LMIC). Methods We assessed rates of ACS in 7 sites in 6 LMIC participating in the Eunice Kennedy Shriver National Institute of Child Health and Human Development's Global Network for Women and Children's Health Research Antenatal Corticosteroids Trial (ACT), a cluster-randomized trial to assess the feasibility, effectiveness, and safety of a multifaceted intervention designed to increase the use of ACS. We conducted this analysis using data from the control clusters, which did not receive any components of the intervention and intended to follow usual care. We included women who delivered an infant with a birth weight <5th percentile, a proxy for preterm birth, and were enrolled in the Maternal Newborn Health (MNH) Registry between October 2011 and March 2014 in all clusters. A survey of the site investigators regarding existing policies on ACS in health facilities and for health workers in the community was part of pre-trial activities. Results Overall, of 51, 523 women delivered in control clusters across all sites, the percentage of <5th percentile babies ranged from 3.5 % in Kenya to 10.7 % in Pakistan. There was variation among the sites in the use of ACS at all hospitals and among those hospitals having cesarean section and neonatal care capabilities (bag and mask and oxygen or mechanical ventilation). Rates of ACS use for <5th percentile babies in all hospitals ranged from 3.8 % in the Kenya sites to 44.5 % in the Argentina site, and in hospitals with cesarean section and neonatal care capabilities from 0 % in Zambia to 43.5 % in Argentina. ACS were rarely used in clinic or home deliveries at any site. Guidelines for ACS use at all levels of the health system were available for most of the sites. Conclusion Our study reports an overall low utilization of ACS among mothers of <5th percentile infants in hospital and clinic deliveries in LMIC. Trial Registration clinicaltrials.gov (NCT01084096 )